2021
DOI: 10.3390/diagnostics11071249
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial, Immunothrombotic, and Inflammatory Biomarkers in the Risk of Mortality in Critically Ill COVID-19 Patients: The Role of Dexamethasone

Abstract: Endothelial dysfunction, coagulation and inflammation biomarkers are increasingly emerging as prognostic markers of poor outcomes and mortality in severe and critical COVID-19. However, the effect of dexamethasone has not been investigated on these biomarkers. Hence, we studied potential prognostic biomarkers of mortality in critically ill COVID-19 patients who had either received or not dexamethasone. Biomarker serum levels were measured on intensive care unit (ICU) admission (within 24 h) in 37 dexamethasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 30 publications
1
59
1
Order By: Relevance
“…Very low quality: we are very uncertain about the estimate. 1 Downgraded for risk of bias and imprecision (95% CI includes line of no effect); 2 downgraded twice for risk of bias; 3 downgraded for risk of bias, imprecision, and inconsistency (due to heterogeneity); 4 downgraded for risk of bias and inconsistency; 5 downgraded for risk of bias, inconsistency, and indirectness.…”
Section: High-risk Population (Severe Disease)mentioning
confidence: 99%
See 1 more Smart Citation
“…Very low quality: we are very uncertain about the estimate. 1 Downgraded for risk of bias and imprecision (95% CI includes line of no effect); 2 downgraded twice for risk of bias; 3 downgraded for risk of bias, imprecision, and inconsistency (due to heterogeneity); 4 downgraded for risk of bias and inconsistency; 5 downgraded for risk of bias, inconsistency, and indirectness.…”
Section: High-risk Population (Severe Disease)mentioning
confidence: 99%
“…Several drugs have been considered for the treatment of SARS-CoV-2, and various unconventional treatments have been hailed as potential cures for COVID-19 [ 1 , 2 , 3 , 4 ]. One of the latest putative silver bullets against COVID-19 is ivermectin [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain blood-based biomarkers, such as lymphocyte, neutrophil and platelet counts, neutrophil-tomonocyte ratio (NMR), neutrophil-to-lymphocyte ratio (NLR), D-dimer, interleukin-6, C-reactive protein (CRP) levels and lactate dehydrogenase (LDH) may discriminate between severe and non-severe COVID-19 (4,7,8). Another biomarker, the soluble urokinase plasminogen activator receptor (suPAR), has been shown to be significantly elevated in patients with COVID-19 (9), and stands out as a predictor of overall disease severity and outcome (10)(11)(12)(13)(14)(15) and in particular of severe respiratory failure (16), and acute kidney injury (17) due to SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The clinical benefits noted with the use of Tocilizumab and Dexamethasone were attributed to the immunomodulation at the level of the endothelium. 18,19 Byttebier et. al demonstrated in a retrospective study that the concurrent treatment with statins, aspirin, and ACE/ARBs, which have protective effects on the endothelium, resulted in a 3-fold reduction in the odds of hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues to be a global challenge worldwide. Although considered at its emergence as a respiratory infection, recent studies demonstrated tropism towards endothelial cells.…”
Section: Introductionmentioning
confidence: 99%